2023
DOI: 10.23865/arctic.v14.4052
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Control and Strategies to Reduce Operational Risk in Russian Extractive Industries Along the Northern Sea Route

Abstract: Russian resource developers operating in remote parts of the Arctic have demonstrated over the past several years that it is feasible to extract natural resources throughout the year, and ship large quantities of raw materials with regular intervals from the Arctic to international markets; this despite very difficult operational conditions in the Arctic during both winter and spring. Several resource extraction projects are currently being implemented or planned. This study examines how the extractive compani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Strategic HRM effectiveness is essential for public sector agencies during commercialization and corporatization, offering a framework for practitioners to add value in the HRM function (Teo & Crawford, 2005). Moreover, the expansion of shipping in the Arctic requires efficient coordination between resource extractive companies and their shipping component, necessitating the adaptation of supply chain management strategies to reduce operational risks (Gunnarsson & Lasserre, 2023).…”
Section: Challenges In Strategic Hrm In the Logistics And Shipping Se...mentioning
confidence: 99%
“…Strategic HRM effectiveness is essential for public sector agencies during commercialization and corporatization, offering a framework for practitioners to add value in the HRM function (Teo & Crawford, 2005). Moreover, the expansion of shipping in the Arctic requires efficient coordination between resource extractive companies and their shipping component, necessitating the adaptation of supply chain management strategies to reduce operational risks (Gunnarsson & Lasserre, 2023).…”
Section: Challenges In Strategic Hrm In the Logistics And Shipping Se...mentioning
confidence: 99%
“…The country has demonstrated that it is technically and financially feasible to extract natural resources throughout the year from remote parts of the Arctic and ship large quantities of raw materials along its Arctic coast to international markets. Russia's focus on the high Arctic underlines the increasing importance of Arctic export terminals for Russia's future extractive industries and energy policy (Gunnarsson & Lasserre, 2023).…”
Section: Russian Federationmentioning
confidence: 99%